Does a Photocatalytic Synergy in an Anatase-Rutile TiO2 Composite Thin-Film Exist? - Kafizas,A; Carmalt,CJ; Parkin,IP (Chemistry - A European Journal, 2012)
It has often been suggested that anatase-rutile mixtures/composites synergistically enhance photocatalysis. However, in the case of dense thin-films containing an intimate mix of both anatase and rutile phases, such an effect has not been observed. In synthesising combinatorial films with graded film thickness and phase, and applying established photocatalytic mapping methods, we were able to assess how dense thin-films of intimately mixed anatase-rutile mixtures affect photocatalytic performance. We found that no photocatalytic synergy between anatase-rutile composites (29≤rutile %≤83) within such dense thin-film systems exists. In fact, an increased presence of rutile caused the photocatalytic activity to fall. This was explained by the unfavourable energetics in the multiple electron transfers required between several neighbouring rutile and anatase sites for the photo-generated electron to reach the material’s surface; encouraging the trapping of electrons within the bulk and increasing the likelihood of charge recombination. The decrease in photocatalytic activity was found to vary linearly with rutile component.